Concurrent encephalopathy and peripheral neuropathy: A rare case of metronidazole toxicity - Shah, Bhupendra; Paudel, Raju; Manandhar, Nawli; Thapa, Paras; Sharma, Vivek; Paudel, Sharma (Grande Medical Journal, 2021)
Metronidazole is a nitroimidazole antibiotic widely used in clinical practice for anaerobic bacteria and protozoa. Though well tolerated, it rarely has severe neurological toxicity. We are reporting a case of a 59-year old female with liver abscess who developed concurrent encephalopathy and peripheral neuropathy after a few days of high-dose metronidazole therapy. MRI brain of patient showed characteristic hyperintense lesion in bilateral dentate nuclei of cerebellum. Nerve conduction study showed demyelinating pattern and sensory neuropathy predominantly affecting lower limbs. The patient recovered well after the withdrawal of the offending agent.